Sagot :
Answer:
1.) 4x² = 2x + 6
Standard Form: 4x² - 2x - 6 = 0
a = 4 ; b = -2 ; c = -6
2.) 11x = 3x² - 9
Standard Form: -3x² + 11x + 9 = 0
a = -3 ; b = 11 ; c = 9
3.) 2x² - 7x - 8 = 12
Standard Form: 2x² - 7x - 20 = 0
a = 2 ; b = -7 ; c = -20
4.) 3x(1 - 2x) = 16
3x - 6x² = 16
Standard Form: -6x² + 3x - 16 = 0
a = -6 ; b = 3 ; c = -16
5.) x² + 3x(x - 2) = 5
x² + 3x² - 6x = 5
Standard Form: 4x² - 6x - 5 = 0
a = 4 ; b = -6 ; c = -5
6.) x + 2 = (2 - x²)
Standard Form: x² + x = 0
a = 1 ; b = 1 ; c = 0
7.) x² - x - 3 = 4x² - 5
x² - 4x² - x - 3 + 5 = 0
-3x² - x + 2 = 0
Standard Form: -3x² - x + 2 = 0
a = 3 ; b = -1 ; c = 2
8.) 2x(9 - 5x) = -5x(2 - 3x)
18x - 10x² = -10x + 15x²
-10x² - 15x² - 18x + 10x = 0
-25x² - 8x = 0
Standard Form: -25x² - 8x = 0
a = -25 ; b = -8 ; c = 0
9.) x(x + 2) - 10 = x(7 - 2x)
x² + 2x - 10 = 7x - 2x²
x² + 2x² - 7x - 10 = 0
3x² - 7x - 10 = 0
Standard Form: 3x² - 7x - 10 = 0
a = 4 ; b = -7 ; c = -10
10.) 3x(2 + 2x) = x(5x - 5)
6x + 6x² = 5x² - 5x
x² + 11x = 0
Standard Form: x² + 11x = 0
a = 1 ; b = 11 ; c = 0